Mobility of savings and investment in Mexico - Gollás, Manuel (Estudios Económicos de El Colegio de México, 1999)
A number of empirical studies have concluded that capital is internationally immobile. This result contradicts the empirical observation that a large volume of capital is traded every day in international capital markets. Is capital internationally mobile or not? This is the well-known Feldstein-Horioka paradox. By estimating savings retention coefficients, we find that in Mexico, capital was immobile during the 1960's and 1970's but mobile during the 1980's and 1990's.